2009
DOI: 10.3109/07357900903095623
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile Associated with Oncogenic Ras-induced Senescence, Cell Death, and Transforming Properties in Human Cells

Abstract: We developed inducible and constitutive expression systems of Ha-RasV12 in HEK 293 cells to examine early oncogenic RasV12 signaling. Inducible expression of oncogenic Ras-triggered growth arrest, early senescence, and later apoptosis. Gene expression profile analysis revealed early Ras proliferation and cell cycle genes like c-fos, cyclin E, cdk2, cell-cell contact, and signaling like integrin a6, MEK5, and free radical signaling genes, like proline oxidase. Therefore, Ras-mediated signaling is a fine regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In contrast to hyper-methylation that suppresses the translation of genes, hypomethylation enables genes to be "released" and start replication and translation. These abnormally expressed proteins trigger an intracellular response, much like hyperexpression of Ras in mammal MSCs triggers activation of tumor suppression pathways, and thus induces irreversible growth arrest (Moumtzi, 2010). In the presence of the hyperproliferative signals during the process of senescence, cells encounter a strong DNA replication stress and finally develop numerous double-stranded DNA breaks (DSBs) in fragile areas of DNA (Hladik, 2019).…”
Section: Oncogene-induced Senescencementioning
confidence: 99%
“…In contrast to hyper-methylation that suppresses the translation of genes, hypomethylation enables genes to be "released" and start replication and translation. These abnormally expressed proteins trigger an intracellular response, much like hyperexpression of Ras in mammal MSCs triggers activation of tumor suppression pathways, and thus induces irreversible growth arrest (Moumtzi, 2010). In the presence of the hyperproliferative signals during the process of senescence, cells encounter a strong DNA replication stress and finally develop numerous double-stranded DNA breaks (DSBs) in fragile areas of DNA (Hladik, 2019).…”
Section: Oncogene-induced Senescencementioning
confidence: 99%
“…Numerous investigations were based e.g. on transcriptome (Huang et al, 2003; Moumtzi et al, 2010; Tchernitsa et al, 2004; Zuber et al, 2000), proteome (Li et al, 2016; Rignall et al, 2009), membrane proteome (Martinko et al, 2018), the secretome (Demory Beckler et al, 2013), glycoproteome (Sudhir et al, 2012) and metabolome analysis (Hutton et al, 2016). In addition, RAS pathway-associated gene signatures were described in cancer cell lines and tumour tissue (Bild et al, 2006; Li et al, 2016; Loboda et al, 2010; Rignall et al, 2009; Stephens et al, 2017; Sweet-Cordero et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This form of senescence, called "oncogene-induced senescence" (oncogene induced CS), is displayed by a variety of cell types (17). Oncogene induced CS is rapidly activated when oncogenic stress is present, resulting in the death of neoplastic cells in vitro (18). However, the role of oncogene induced CS in vivo is not clear, although data gathered by some authors have shown that oncogene induced CS could also serve as an in vivo antitumoral mechanism.…”
Section: Introductionmentioning
confidence: 99%